Entry-Level Assessment to Assess Readiness and Predict Study Success of Prospective College Students - Imam Agus Basuki; Imam Suyitno; Maulidina Ahsani (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aimed to evaluate the effectiveness of the Entry-Level Assessment (ELA) in measuring academic readiness and predicting the success of new students during their first year of study. The research utilized a mixed-methods approach, integrating qualitative analysis to describe the characteristics of test items with quantitative analysis to explore the relationship between ELA scores and academic achievement, as reflected in first and second-semester grade point averages (GPA). Data were gathered from ELA documents, ELA scores, and the GPAs of 132 students. The findings demonstrated that the ELA encompasses tests assessing academic potential, literacy, numeracy, and English, with a particular focus on higher-order thinking skills. Correlation analysis revealed a positive relationship between ELA scores and GPA in the first semester; however, this correlation weakened in subsequent semesters. These findings affirm that the ELA possesses strong predictive validity for short-term academic success but has limitations in forecasting long-term performance. This study makes a significant contribution to the advancement of college entrance tests by recommending enhancements in item design, improving the relevance of cognitive indicators, and broadening the assessment framework to include social and emotional skills. The implications of these findings are vital for higher education institutions in developing their selection policies and supporting students' academic journeys.